2000
DOI: 10.1046/j.1537-2995.2000.40080961.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro collection and posttransfusion engraftment characteristics of MNCs obtained by using a new separator for autologous PBPC transplantation

Abstract: The mean Amicus CD34+ cell collection efficiency was better (p<0.05) than that of the CS-3000 Plus collection. Short-term engraftment was durable. The PBPCs collected with the Amicus separator are safe and effective for use for autologous transplant patients requiring PBPC rescue from high-dose myeloablative chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
49
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 9 publications
6
49
5
Order By: Relevance
“…11 The more aggressive settings were used by Ikeda et al when comparing the AM to the SP. 15 They found equivalent CD34 þ cell yields, white blood cell content, mononuclear cell content and colony-forming units granulocyte/macrophage (CFU-GM). They found similar collection efficiencies for CD34 þ cells, white blood cells and mononuclear cells but significantly lower collection efficiencies for platelets.…”
Section: Discussionmentioning
confidence: 98%
“…11 The more aggressive settings were used by Ikeda et al when comparing the AM to the SP. 15 They found equivalent CD34 þ cell yields, white blood cell content, mononuclear cell content and colony-forming units granulocyte/macrophage (CFU-GM). They found similar collection efficiencies for CD34 þ cells, white blood cells and mononuclear cells but significantly lower collection efficiencies for platelets.…”
Section: Discussionmentioning
confidence: 98%
“…Apheresis devices have progressively improved in recent years and newly introduced cell separators show an improved collection eciency (CE), a higher purity of MNC, and lower platelets contamination [6,7]. A study comparing six dierent cell separators showed that MNC CE varied from 38 to 71% [1] and a study conducted in a pediatric setting comparing three dierent devices showed that CD34+ cells CE ranged from 42 to 51% [4].…”
Section: Discussionmentioning
confidence: 99%
“…Snyder et al showed a very good performance of the system in leukaphereses of mobilized and nonmobilized adult patients and donors [2,3]. With extended use of this system, its characteristics were described in more detail.…”
Section: Introductionmentioning
confidence: 99%